Xerostomia: a silent burden for people receiving palliative care – a qualitative descriptive study - Emir Murphy Dourieu; Dominika Lisiecka; William Evans; Patricia Sheahan (BMC Palliative Care)
Abstract Background The prevalence of dry mouth in the palliative care population is well documented and increases due to polypharmacy, radiotherapy and systemic conditions. Saliva as a lubricant for the mouth and throat has implications for swallowing, chewing, and speech. The literature about the experience of xerostomia (perceived feeling of dry mouth) in palliative care is scarce. Clinical evidence suggests that xerostomia has a negative impact on people’s comfort, however, no recent studies explored this impact in detail. This new knowledge is paramount to adhere to the principles of palliative care. Aims To evaluate the impact of xerostomia on the lives of people receiving palliative care with particular reference to eating and speaking.  Design A qualitative descriptive study (interview design). Thematic analysis was used for data analysis. Setting A single specialist palliative care centre in Ireland. Results The majority of participants (35/40) had cancer. Xerostomia was reported to have multiple physical, psychological, and daily life consequences. Participants provided insights into the impact of xerostomia on sleeping, eating, talking, denture wearing, and they described in detail their intra-oral sensations associated with xerostomia. The negative effect of xerostomia on speech was reported as the most significant to participants. Conclusion Xerostomia has a profound impact on the daily lives of people receiving palliative care, including physical and psychological consequences. Speaking is often affected, which can impede the person’s ability to communicate. There needs to be increased awareness of the impact of xerostomia and more research is required to understand how best to manage xerostomia in a palliative care setting.